Minor modifications to the structure of tunicamycin lead to loss of the biological-activity of the antibiotic - Hashim, Onn Haji; Cushley, W. (1987)
Three analogues of tunicamycin, each with minor alterations in structure in different regions of the molecule, have been employed to study the effects of such modifications upon the biological activity of the antibiotic. The data indicate that any modification of structure results in loss of the ability of the antibiotic to inhibit N-glycosylation of proteins. In contrast to tunicamycin itself, none of the analogues had any deleterious effects upon cellular macromolecule synthesis, nor upon the kinetics of export of de novo synthesised IgM or IgG molecules from treated rat hybridoma cells. In addition, the incorporation of tritiated sugars into acid-precipitable macromolecules was not inhibited. Endoglycosidase H digestion of isolated IgG molecules further suggested that the analogues employed did not interfere with qualitative glycosylation at the level of N-acetylglucosamine transferases I and II in the golgi apparatus. The data are consistent with the interpretation that tunicamycin has very precise structural requirements for expression of inhibitory effects upon protein glycosylation, and that small variations of structure can lead to loss of its inhibitory effects.